Effect of micro-magnesium oxide admixture on rheological and compressive strength properties of class G well cement - Chen, Weiqing; Mahmoud, Ahmed Abdulhamid; Elkatatny, Salaheldin (Frontiers in Materials, 2022)
Rheological property tuning is one of the key aspects of oil well cement not only affecting the cement slurry placement but also indirectly impacting other cementing properties like the bonding strength and compressive strength. However, the research is scant on the rheology properties by blending magnesium oxide with class G oil well cement, despite some studies have been conducted on its impacts on shrinkage compensation, compressive strength, bonding strength, and permeability properties of oil well cement. This work studies the effects of microsized magnesium oxide on the rheological properties and compressive strength of the formulated API Class G oil well cement slurries. Two types of micro-sized magnesium oxide (50 μm, 100 μm) were used as the mineral admixture at different dosages (3 %, 9 %). The base formulated slurry sample was incorporated with the silica flour and several commercialized additives such as retarder, fluid loss control agent, and defoamer. A batch of flow tests have been conducted by use of a digital viscometer at two different temperatures, namely 25 °C and 88 °C. The compressive strength has also been measured after curing the samples with the same formulation and conditions for seven days. The variations of the rheology properties (plastic viscosity, yield stress, gel strength), shear stress - shear rate correlations, and shear thinning/thickening behavior, are impacted by the temperature, the type, and dosage of magnesium oxide. The plastic viscosity of the tested slurries decreased by 27.0 % (type II, 9 %, 25 °C), 15.1 % (type II, 3 %, 88 °C), respectively. And the yield stress increased by 258.5 % (type II, 3 %, 88 °C) and 53.9 % (type II, 9 %, 25 °C). The gel strength generally increases with the magnesium oxide dosage increasing. However, all tested slurry samples show shear-thinning behavior and non- Newtonian characteristics. Among the tested slurry samples, it is found to achieve better rheology performance when incorporating magnesium oxide with a smaller particle size. On the other side, the specimens of mixing magnesium oxide with bigger particle size and medium dosage outperform its rival with a smaller particle size in compressive strength.